1988
DOI: 10.1073/pnas.85.24.9499
|View full text |Cite
|
Sign up to set email alerts
|

Structure and regulation of the rat 1,25-dihydroxyvitamin D3 receptor.

Abstract: Complementary DNA clones encoding the entire rat 1,25-dihydroxyvitamin D3 receptor were isolated, and the total 423-amino acid sequence was deduced. The amino acid sequence of the rat receptor is similar but not identical to the reported human receptor sequence. The cysteine-rich DNA-binding domain is completely conserved and the steroidbinding domain is >93% conserved between rat and human. The cDNA was used as a probe in blot analysis of polyadenylylated RNA to show that the 1,25-dihydroxyvitamin D3 receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 19 publications
1
43
0
1
Order By: Relevance
“…(hGR) Human glucocorticoid receptor (Hollenberg et al 1985); {hER) human estrogen receptor Greene et al 1986); (cERBA) chicken c-erbA thyroid hormone receptor (Sap et al 1986); {rVDR) rat vitamin D receptor (Burmester et al 1988); (hRAR) human retinoic acid receptor (Giguere et al 1987); ( which we call El, E2, and E3. The E1 subregion is the most highly conserved and corresponds to a region shown by in vitro mutagenesis to be essential for steroid binding and steroid-dependent trans-activation (Giguere et al 1986;Danielson et al 1987}.…”
Section: Discussionmentioning
confidence: 99%
“…(hGR) Human glucocorticoid receptor (Hollenberg et al 1985); {hER) human estrogen receptor Greene et al 1986); (cERBA) chicken c-erbA thyroid hormone receptor (Sap et al 1986); {rVDR) rat vitamin D receptor (Burmester et al 1988); (hRAR) human retinoic acid receptor (Giguere et al 1987); ( which we call El, E2, and E3. The E1 subregion is the most highly conserved and corresponds to a region shown by in vitro mutagenesis to be essential for steroid binding and steroid-dependent trans-activation (Giguere et al 1986;Danielson et al 1987}.…”
Section: Discussionmentioning
confidence: 99%
“…Shown are sequences from human (Hu), (147) mouse (Mus musculus, abbreviated Ms), (149) chicken (Gallus gallus, denoted Ch), (1,150,151) and Xenopus laevis (Xl). (18) Numbering is for the hVDR as published by Baker et al (147) Not shown are sequences from rat (148) and Japanese quail, (151) which are similar to the mouse and chicken, respectively. Alternative translation start sites for chicken (Ch) or human (Hu) mRNAs are indicated by arrows.…”
Section: Dna Bindingmentioning
confidence: 99%
“…To date, VDR cDNAs have been cloned from six species, namely human, (147) rat, (148) mouse, (149) chicken, (1,150,151) Japanese quail, (151) and frog (Xenopus laevis). (18) As illustrated in Fig.…”
Section: Comparison Of Vdrs Across Speciesmentioning
confidence: 99%
“…Like the other members of this receptor family, VDR is comprised of at least two functional domains, a steroid hormone-binding domain and a DNA-binding domain (17)(18)(19)(20)(21)(22)(23). The steroid-binding domain stretches from amino acid 182 to the COOH-terminus at amino acid 427 and provides the molecule with high affinity, steroid-specific recognition of the 1,25(OH)2D3 metabolite.…”
mentioning
confidence: 99%
“…1,25(OH)2D3 binding to the steroid-binding domain of the receptor "activates" the VDR to a form with high affinity for DNA. The DNA-binding domain of the VDR then binds to a vitamin D response element in the regulatory region of target genes to modulate transcription of responsive genes and thereby mediates hormone action (17)(18)(19)(20)(21)(22)(23).Progress to elucidate the molecular basis of HVDRR began with the demonstration that rodent skin possessed VDR (24, 25) and that cultured human dermal fibroblasts derived from skin biopsies could be used as a model system for the study of the VDR from patients (26). It was soon demonstrated that defects in the VDR were the likely cause of the HVDRR syndrome (5) and that different families exhibited different defects (5-16).…”
mentioning
confidence: 99%